(untitled) (Indian Journal of Arid Horticulture, 2025)
The guava is a tropical fruit that originated in Central and South America and has since been grown in many tropical and subtropical areas worldwide. In these regions, guava fruit fly, Bactrocera correcta, is a noteworthy pest of guava and other fruits. This particular species of fruit fly lays its eggs in ripening or ripe fruits of guavas, which may culminate in infestations which significantly damage crops. The female guava fruit fly normally releases the eggs within the fruit as part of the life cycle. After hatching, the larvae feed the fruit pulp, which makes it rot and unfit for human eating. In cases of severe infestation, this not only diminishes the fruit’s yield and quality but also makes it unmarketable. Controlling the guava fruit fly often involves a combination of cultural, mechanical, biological, and chemical methods. These can include techniques such as fruit bagging, sanitation, trapping, para-pheromone lure, bait spray, biocontrol, bio-pesticide and the application of insecticides. Fruit fly populations can be effectively managed by using fewer chemical pesticides and implementing integrated pest management (IPM) techniques. Maintaining the productivity and quality of guava crops, as well as other susceptible fruits in affected areas requires efforts to control the guava fruit fly.